2018
DOI: 10.22179/revmacn.20.605
|View full text |Cite
|
Sign up to set email alerts
|

Development of microconsumers in waterlogged soil: experience in microcosms

Abstract: Los ríos de llanura tienen como característica particular presentar una interrelación con su valle de inundación y con los ambientes lénticos asociados a él (Amoros & Bornette, 2002; Vázquez et al., 2008). durante las inundaciones grandes, cantidades de sedimento son desplazados por los ríos y en esos sedimentos existe una gran variedad de estadios de resistencia. Pequeñas inun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nitrates and nitrites increased gradually during the experiment, owing to the endogenous nitri cation processes and the incorporation of water to maintain the water level of the mesocosm. Nevertheless, the previous investigations involving a long ooding period in lentic systems (Quaíni 2011;Solari et al 2018;Zaplara et al 2023) observed that the water nitrate decreased markedly for up to 15 days and remained very low thereafter. This nding was attributable to a consumption by the producing microorganisms, which registered a substantial development until the end of the ooding, and also coincided with the observed decrease in SRP.…”
Section: Nutrients and Chlorophyll "A"mentioning
confidence: 86%
See 2 more Smart Citations
“…Nitrates and nitrites increased gradually during the experiment, owing to the endogenous nitri cation processes and the incorporation of water to maintain the water level of the mesocosm. Nevertheless, the previous investigations involving a long ooding period in lentic systems (Quaíni 2011;Solari et al 2018;Zaplara et al 2023) observed that the water nitrate decreased markedly for up to 15 days and remained very low thereafter. This nding was attributable to a consumption by the producing microorganisms, which registered a substantial development until the end of the ooding, and also coincided with the observed decrease in SRP.…”
Section: Nutrients and Chlorophyll "A"mentioning
confidence: 86%
“…Recent investigations (Zaplara et al 2023) have demonstrated that upon ooding a soil under lentic conditions over a short time, mediated by different physical-chemical procedures, the soil releases the adsorbed phosphorus into the water (Zaplara et al 2023) to become a source of nutrients for oxygenproducing organisms and for the upper trophic chains. In lentic systems, when a soil is ooded, the water displaces the air in the pores between the soil particles, thus reducing the availability of oxygen and generating anoxic sites (Rubio et al 1997;Chaneton 2006).…”
Section: Nutrients and Chlorophyll "A"mentioning
confidence: 99%
See 1 more Smart Citation